Persepsi Mahasiswa pada Kepuasan Program Magang di Industri Pariwisata - Muhamad Panji Fadlan; Nidia Wulansari (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
This study explores students' perceptions of internship program satisfaction within the tourism industry, prompted by complaints from several students who felt dissatisfied with the internship programs they had participated in. This quantitative research employs a survey method with a total sampling (census) technique, involving 148 respondents. Data collection was carried out using a questionnaire with a Likert scale that had been tested for validity and reliability. The data analysis techniques include data description, interval value limitation, and Mean Score tests, utilizing SPSS version 23.00 and Microsoft Excel 2016. The findings of this study indicate that students' perceptions of the campus are considered very good with a score of 3.42, perceptions of the industry are regarded as good with a score of 3.25, and perceptions of personal development are viewed as very good with a score of 3.59.